PENGARUH PERENDAMAN DAN KEDALAMAN PENANAMAN TERHADAP PERKECAMBAHAN BENIH MAHONI (Swietenia macrophylla) - Malik Ibrahim Yasin; Basir Basir; Gusti Syeransyah Rudy (Universitas Lambung Mangkurat, 2022)
The purpose of this study was to analyze the speed of germination and the percentage of germination of mahogany seeds. The factors studied were immersion and planting depth. The immersion factor consisted of no soaking, soaking with young coconut water, soaking with onion extract, soaking with bean sprouts water, and soaking with warm water. The depth factor consists of 1 cm and 2 cm. This study used a completely randomized design with a factorial pattern. The results showed that the immersion factor had a significant effect on the variable speed of germination of mahogany seeds. The treatment of soaking seeds with bean sprouts water was the best treatment for germination at a rate of 24,17 days. The effect of this treatment was significantly different from the effect of onion extract and without soaking which resulted in slow germination of seeds, which were 33,17 days and 35,67 days, respectively. The depth factor has a very significant effect on the speed of germination, namely the planting depth of 2 cm was better than 1 cm with the germination speed of 23,53 days and 36.07 days, respectively. However, the two factors did not interact for the variable speed of germination. For the percentage of mahogany seed germination variable, the interaction between the immersion factor and the planting depth factor had a very significant effect on the percentage of germination, where without soaking, soaking with young coconut water and soaking seeds with bean sprouts, all of which were planted as deep as 2 cm, resulted in the highest percentage of germination of mahogany seeds, namely 100% which differed significantly from the other treatment interactionsTujuan penelitian ini adalah untuk menganalisis kecepatan berkecambah dan persentase berkecambah benih mahoni. Faktor yang diteliti adalah perendaman dan kedalaman penanaman. Faktor perendaman terdiri dari tanpa perendaman, perendaman dengan air kelapa muda, perendaman dengan ekstrak bawang merah, perendaman dengan air tauge, dan perendaman dengan air hangat. Faktor kedalaman terdiri dari 1 cm dan 2 cm. Penelitian ini menggunakan rancangan acak lengkap dengan pola faktorial. Hasil penelitian menunjukkan bahwa faktor perendaman berpengaruh nyata pada variabel kecepatan berkecambah benih mahoni. Perlakuan perendaman benih dengan air tauge merupakan perlakuan terbaik untuk perkecambahan dengan kecepatan 24,17 hari. Perlakuan ini pengaruhnya berbeda nyata dengan pengaruh ekstrak bawang merah dan tanpa perendaman yang menghasilkan benih yang lambat berkecambah, yaitu masing-masing 33,17 hari dan 35,67 hari. Faktor kedalaman berpengaruh sangat nyata terhadap kecepatan berkecambah, yaitu kedalaman tanam 2 cm lebih baik dari 1 cm dengan kecepatan berkecambah masing-masing 23,53 hari dan 36,07 hari. Namun kedua faktor tersebut tidak terjadi interaksi untuk variable kecepatan berkecambah. Untuk variabel persentase berkecambah benih mahoni, interaksi antara faktor perendaman dan faktor kedalaman tanam berpengaruh sangat nyata terhadap persentase berkecambah, dimana tanpa perendaman, perendaman dengan air kelapa muda dan perendaman benih dengan tauge yang kesemuanya ditanam sedalam 2 cm menghasilkan persentase berkecambah benih mahoni paling tinggi yaitu 100% yang berbeda sangat dengan interaksi perlakuan lainnya